FGFR1 underlies obesity-associated progression of estrogen receptor–positive breast cancer after estrogen deprivation - Elizabeth A. Wellberg; Peter Kabos; Austin E. Gillen; Britta M. Jacobsen; Heather M. Brechbuhl; Stevi J. Johnson; Michael C. Rudolph; Susan M. Edgerton; Ann D. Thor; Steven M. Anderson; Anthony Elias; Xi Kathy Zhou; et al. (JCI Insight, 2018)
Obesity increases breast cancer mortality by promoting resistance to therapy. Here, we identified regulatory pathways in estrogen receptor–positive (ER-positive) tumors that were shared between patients with obesity and those with resistance to neoadjuvant aromatase inhibition. Among these was fibroblast growth factor receptor 1 (FGFR1), a known mediator of endocrine therapy resistance. In a preclinical model with patient-derived ER-positive tumors, diet-induced obesity promoted a similar gene expression signature and sustained the growth of FGFR1-overexpressing tumors after estrogen deprivation. Tumor FGFR1 phosphorylation was elevated with obesity and predicted a shorter disease-free and disease-specific survival for patients treated with tamoxifen. In both human and mouse mammary adipose tissue, FGF1 ligand expression was associated with metabolic dysfunction, weight gain, and adipocyte hypertrophy, implicating the impaired response to a positive energy balance in growth factor production within the tumor niche. In conjunction with these studies, we describe a potentially novel graft-competent model that can be used with patient-derived tissue to elucidate factors specific to extrinsic (host) and intrinsic (tumor) tissue that are critical for obesity-associated tumor promotion. Taken together, we demonstrate that obesity and excess energy establish a tumor environment with features of endocrine therapy resistance and identify a role for ligand-dependent FGFR1 signaling in obesity-associated breast cancer progression.